An Analysis of Factors Related to the Preparedness of Health Workers at the Harian Community Health Center, Samosir Regency - Gultom, Jonri; Rinawati Sembiring; Janno Sinaga; Kesaktian Manurung; Donal Nababan (JURNAL KESMAS DAN GIZI (JKG), 2026)
Health workers at primary health care facilities, such as community health centers (puskesmas), play a crucial role in all phases of disaster management. However, their preparedness often remains suboptimal due to limited training, experience, and coordination capacity. This study aimed to analyze factors associated with disaster preparedness among health workers at Harian Community Health Center, Samosir Regency. A quantitative research with a cross-sectional design was applied. The total population of 51 health workers was included using a total sampling technique. Data were collected using a structured questionnaire validated for reliability and accuracy, and analyzed using chi-square and multiple logistic regression tests. The results showed significant relationships between disaster management training (p=0.043), involvement in disaster response (p=0.008), participation in the Rapid Response Team (TGC) (p=0.012), knowledge (p=0.035), and attitude (p=0.049) with disaster preparedness. In contrast, age (p=0.471), gender (p=1.000), education level (p=0.323), and work experience (p=0.750) were not significantly related. Multivariate analysis identified participation in the TGC as the most dominant factor influencing preparedness, with Exp(B) = 21.635. These findings highlight the need to strengthen disaster preparedness at the primary care level through regular training, simulation exercises, and empowerment of TGC teams as key components of the health emergency response system